2003
DOI: 10.1148/radiol.2292030736
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome: Relationship between Radiologic and Clinical Parameters

Abstract: Severity of lung abnormalities quantified on chest radiographs correlates with clinical and laboratory parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
1

Year Published

2003
2003
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 15 publications
4
31
1
Order By: Relevance
“…The characterstic HRCT features upon presentation were ground-glass opacities, sometimes with consolidation, and were associated with interlobular and intralobular septal thickenings. It has also been shown that radiographic and HRCT appearances were correlated to clinical and laboratory parameters [41,42]. [60,61].…”
Section: (B) Early Outcomes Of Sarsmentioning
confidence: 97%
“…The characterstic HRCT features upon presentation were ground-glass opacities, sometimes with consolidation, and were associated with interlobular and intralobular septal thickenings. It has also been shown that radiographic and HRCT appearances were correlated to clinical and laboratory parameters [41,42]. [60,61].…”
Section: (B) Early Outcomes Of Sarsmentioning
confidence: 97%
“…Radiographical, haematological, biochemical and microbiological evaluation A chest radiograph, complete blood counts, alanine transaminase (ALT) and renal function tests were performed daily [13]. Chest radiographs were scored according to the per cent of lung involvement in each lung (05normal, 1510%, 2520%, 105100% involvement).…”
Section: Patient Recruitment and Study Designmentioning
confidence: 99%
“…A radiographic progress was regarded as improved, unchanged or deteriorated if the radiographical score (within 5%) on day 3 was ,, equal to, or . that derived on day 1, respectively [13]. Symptoms, travel and contact history were prospectively obtained by infection control nurses with a standardised questionnaire.…”
Section: Patient Recruitment and Study Designmentioning
confidence: 99%
“…have abnormal chest radiographs, all of which show airspace consolidation that initially tends to be peripheral and lower zone in distribution [29][30][31]. Whilst most patients have abnormal chest radiograph on presentation, the patterns are usually no cavitation, hilar lymphadenopathy or pleural effusion at presentation [32].…”
Section: Bedside and Clinical Diagnosis Of Severe Acute Respiratory Smentioning
confidence: 99%
“…Whilst most patients have abnormal chest radiograph on presentation, the patterns are usually no cavitation, hilar lymphadenopathy or pleural effusion at presentation [32]. Generally, radiographical opacities peak 8-10 days after the onset of illness when bilateral disease is usually the case, and radiographic severity tends to correlate with clinical and laboratory parameters, such as oxygen saturation and liver transaminases [15,30,31]. Pneumomediastinum and pneumothoraces, often spontaneous but also occur with assisted ventilation, could complicate extensive disease ( fig.…”
Section: Bedside and Clinical Diagnosis Of Severe Acute Respiratory Smentioning
confidence: 99%